PERAN GURU IPA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI SMP NEGERI 4 PEMATANG SIANTAR - Damanik, Nellawani; Perayanti Sinaga, Dian; Rosenta Purba, Ika (Jurnal Metabio, 2023)
The world of education deserves serious attention regarding children's character. Recent problems in our country are inextricably linked to character issues. According to Law No. 20 of 2003 concerning education, it is a conscious and planned effort in the development and learning process for individuals to grow and develop into independent, responsible, creative, knowledgeable, healthy, and virtuous individuals. This research method can also be considered a problem-solving strategy. This stage provides an overview of how a research problem can be described and answers found. The type of research used in this study is descriptive, which attempts to describe the research object in depth based on the facts as they appear. This study uses a qualitative approach to obtain an overview of the objectives. The study, entitled "The Role of Science Teachers in Building Student Character," demonstrates that teachers' roles in character formation are carried out through questioning skills, the use of media and learning aids, and the closing of learning skills. The teacher's role is crucial in shaping students' character in participating in learning activities. Students' interest and enjoyment in participating in learning activities are also important.